Pengabdian Masyarakat: Edukasi Psikososial sebagai Upaya Meningkatkan Kualitas Hidup pada Nelayan dengan Kanker Kulit Melanoma di Galesong Takalar, Makassar, Sulawesi Selatan - Irma Fajriah (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
Melanoma is a type of malignant skin cancer commonly found among fishing communities due to prolonged exposure to ultraviolet radiation. Initial observations in the coastal area of Galesong, Takalar, South Sulawesi, revealed that many fishermen exhibit symptoms of skin cancer yet have low levels of knowledge and awareness regarding prevention and treatment. This community service activity aimed to provide psychosocial education to improve the quality of life for patients and their families. The methods included health education sessions, group counseling, and the distribution of culturally relevant educational materials. The results showed increased participant understanding of melanoma skin cancer, strengthened family psychosocial support, and greater motivation to seek routine health check-ups. This program is expected to serve as a community-based promotive and preventive intervention model for addressing skin cancer in high-risk groups.